The Solvability and Optimal Controls for Some Fractional Impulsive Equations of Order 1< α<2 - Xianghu Liu; Zhenhai Liu; Maojun Bin (Abstract and Applied Analysis)
We study the existence of solutions and optimal controls for some fractional impulsive equations of order 1< α<2. By means of Gronwall’s inequality and Leray-Schauder’s fixed point theorem, the sufficient condition for the existence of solutions and optimal controls is presented. Finally, an example is given to illustrate our main results.